Unified reciprocity of dithiophosphate by dichalcogenophosph(in)ate ligands on copper hydride nanoclusters via ligand exchange reaction. Issue 9 (29th May 2019) - Lin, Po‐Yu; Li, Dai‐Ying; Ho, Feng‐Hsien; Liao, Jian‐Hong; Barik, Subrat Kumar; Liu, C. W.
Abstract: A structural study of ligand exchange on chalcogen‐passivated copper nanoclusters is far less developed. Herein, we report the synthesis of polyhydrido copper nanoclusters [Cu20 H11 {Se2 P(O i Bu)2 }9 ] (2 ) passivated by Se‐donor ligands via ligand replacement reaction on [Cu20 H11 {S2 P(O i Pr)2 }9 ] (1 ) with NH4 [Se2 P(O i Bu)2 ]. In parallel to the synthesis of2, cluster [Cu20 H11 {S2 P(CH2 CH2 Ph)2 }9 ] (4 ) was produced by the ligand exchange reaction on a new derivative of1, that is [Cu20 H11 {S2 P(O n Pr)2 }9 ] (3 ). Solid state structures of both clusters2 and4 were unequivocally established by single‐crystal X‐ray diffraction studies and cluster4 epitomizes exceptional case to preserve both the shape and size of the nanocluster during the course of ligand exchange. Structurally precise cluster2 is the second example where the copper hydride nanocluster is stabilized by Se‐donor ligands. The anatomy of2 can be visualized as a twisted cuboctahedral Cu13 core, two triangular faces of which are capped by a Cu6 cupola and a single Cu atom along the C 3 rotational axis. Abstract : Two new polyhydrido copper nanoclusters, [Cu20 H11 {Se2 P(O i Bu)2 }9 ] and [Cu20 H11 {S2 P(CH2 CH2 Ph)2 }9 ], which are stabilized by Se‐donor and S‐donor ligands, respectively, via ligand exchange reaction on [Cu20 H11 {S2 P(OR)2 }9 ] (R =  i Pr and n Pr), were synthesized and structurally characterized. Se‐donor ligand exchange leads to the alteration of shape and size of the cluster while S‐donor ligand exchange preserves both the cluster shape and size.